1990
DOI: 10.1118/1.596586
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate determination for 125I seeds

Abstract: Dose rates in water have been determined for the two types of 125I seed currently used in brachytherapy. The need for such determinations became evident when water/air ratios measured with a silicon diode were found to be lower than expected. Extensive measurements using lithium fluoride thermoluminescent dosimeters (TLD's) have been performed in a solid water phantom, at distances from 0.1 to 10 cm from the seed center and at angular increments of 10 degrees, 15 degrees, or 30 degrees within a plane through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…For a better understanding of the discrepancies observed in the different data sets we represent in figure 5 the anisotropy as a function of the angle at three different distances. We also included values obtained from the matrix fit to diode measurements in liquid water by Schell et al (1987) and Monte Carlo calculations with MORSE code performed by Chiu-Tsao et al (1990), who modelled the ion-exchange resin beads in the titanium capsule by three spheres symmetrically located with their centres 0.125 cm apart on the seed axis and the titanium capsule as a hollow right circular cylinder. There is an excellent agreement of our results with those of Chiu-Tsao, showing that differences caused by assuming a model of cylindrical resin beads are negligible.…”
Section: Angular Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…For a better understanding of the discrepancies observed in the different data sets we represent in figure 5 the anisotropy as a function of the angle at three different distances. We also included values obtained from the matrix fit to diode measurements in liquid water by Schell et al (1987) and Monte Carlo calculations with MORSE code performed by Chiu-Tsao et al (1990), who modelled the ion-exchange resin beads in the titanium capsule by three spheres symmetrically located with their centres 0.125 cm apart on the seed axis and the titanium capsule as a hollow right circular cylinder. There is an excellent agreement of our results with those of Chiu-Tsao, showing that differences caused by assuming a model of cylindrical resin beads are negligible.…”
Section: Angular Dependencementioning
confidence: 99%
“…Several investigators have reported on the two-dimensional dosimetry of 125 I (Dale 1982, Arcovito et al 1985, Ling et al 1983, Schell et al 1987, Burns and Raeside 1987, Williamson and Quintero 1988, Piermattei et al 1988, Chiu-Tsao et al 1990, Scarbrough et al 1990, Nath et al 1993, Wang and Slovoda 1996, Weaver et al 1989, Weaver 1998) and 103 Pd seeds (Meigooni et al 1990, Chiu-Tsao and Anderson 1991, Nath et al 1995. The AAPM Task Group No 43 (Nath et al 1995) recommends a dosimetry protocol based on measured (or measurable) quantities allowing for two-dimensional dose calculations around cylindrically symmetric sources.…”
Section: Introductionmentioning
confidence: 99%
“…They were able to reduce the uncertainty down to ±15% as compared to the 95% confidence interval of ±25% specified by the manufacturer. 11 Other studies investigated the use of radiochromic films, 10,[12][13][14][15][16][17] TLDs, 15,16,[18][19][20][21][22][23] extrapolation ionization chambers, 24 and diodes 25 which are considered to be a standard for 125 I eye plaque dosimetry. Other dosimetric techniques which are less widely used, such as plastic scintillators, 11,26,27 threedimensional liquid scintillators, 28 and polymer gel dosimetry 29 were explored as well.…”
Section: Introductionmentioning
confidence: 99%
“…Using TLD-100 chips and powder capsules embedded in machined solid-water phantoms, the ICWG developed procedures, for calibrating TLD detectors and correcting for higher TLD response to low-energy photons, for quantitatively estimating absolute dose rates in water. Each of the three ICWG investigator groups independently measured (Chiu-Tsao et al 1990, Weaver et al 1989 transverse-axis dose distributions for the 125 I and 192 Ir then available to validate their TLD measurement methodology. This was followed by more complete 2D dose distributions about the extant 125 I, 192 Ir and 103 Pd brachytherapy sources (Chiu-Tsao and Anderson 1991, Nath et al 1993.…”
Section: Modern Experimental Dosimetry and Calibration Methodsmentioning
confidence: 99%